Pengaruh Perceived Security dan Perceived Ease of Use terhadap Intention to Use Dengan Trust sebagai Intervening pada Penggunaan Aplikasi Pembayaran Digital di Jakarta - Ignasius Falentino Manalu; Basrah Saidani; Shandy Aditya (Fakultas Ekonomi Universitas Negeri Jakarta, 2022)
This study aims to explain a comprehensive model that explains the impact of perceived security and perceived ease of use in influencing intention to use and how they contribute through trust in the context of using digital payment applications in Jakarta. The purpose of this study is to analyze the effect of perceived security on trust, the effect of perceived ease of use on trust, the effect of perceived security on intention to use, the effect of perceived ease of use on intention to use, the effect of trust on intention to use, the effect of perceived security on intention to use through trust, the effect of perceived ease of use on intention to use through trust, as well as the influence of perceived security on intention to use indirect effect through trust and the influence of perceived ease of use on intention to use indirect effect through trust in the use of digital payment applications. Data was collected by using questionnaires online methods to reduce the impact of the covid 19 virus during a pandemic. The object of this research is 150 respondents who are users of digital payment applications. Data analysis to test the validity and reliability using SPSS version 24 and using the Structural Equation Model (SEM) research method with AMOS version 24 to process research data. The results of hypothesis testing show: that perceived security has a significant effect on trust, perceived easeof use has a significant effect on trust, perceived security has a significant effect on the intention to use e payment, perceived ease of use has a significant effect on the intention to use e[1]payment. Trust has a significant effect on the intention to use e payment. Perceived security has a direct significant effect on the intention to use through trust, perceived ease of use does not have a direct significant effect on the intention to use through trust. Perceived security has a significant indirect effect on the intention to use through trust, and perceived ease of use has a significant indirect effect on the intention to use through trust. Penelitian ini bertujuan untuk menjelaskan model komprehensif yang menjelaskan pengaruh dampak perceived security dan perceived ease of use dalam mempengaruhi intention to usedan bagaimana kontribusinya melalui trust dalam konteks penggunaan aplikasi pembayaran digital di Jakarta. Tujuan dari penelitian ini dimaksudkan untuk menganalisis pengaruh perceived security terhadap trust, pengaruh perceived ease of use terhadap trust, pengaruh perceived security terhadap intention to use, pengaruh perceived ease of use terhadap intention to use, pengaruh trust terhadap intention to use, pengaruh perceived security terhadap intention to use melalui trust pengaruh perceived ease of use terhadap intention to use melalui trust, serta pengaruh perceived security terhadap intention to use secara tidak langsung melalui trust dan pengaruh perceived ease of use terhadap intention to use secara tidak langsung melalui trustpada penggunaan aplikasi pembayaran digital. Pengumpulan data dilakukan dengan menggunakan metode penyebaran kuesioner secara online untuk mengurangi dampak penyebaran virus covid 19 selama pandemi. Objek penelitian ini berjumlah 150 responden yang merupakan pengguna aplikasi pembayaran digital. Analisis data untuk uji validitas dan reliabilitas menggunakan SPSS versi 24 dan menggunakan metode penelitian Structural Equation Model (SEM) dengan AMOS versi 24 untuk mengolah data penelitian. Hasil pengujian hipotesis menunjukkan: perceived security berpengaruh signifikan terhadap trust, perceived ease of use berpengaruh signifikan terhadap trust, perceived security berpengaruh signifikan terhadap intention to use e payment, perceived ease of use berpengaruh signifikan terhadap intention to use e payment. Trust berpengaruh signifikan terhadap intention to use e[1]payment. Perceived security berpengaruh signifikan secara langsung terhadap intention to usemelalui trust, perceived ease of use tidak berpengaruh signifikan secara langsung terhadap intention to use melalui trust. Perceived security berpengaruh signifikan secara tidak langsungterhadap intention to use melalui trust, perceived ease of use berpengaruh signifikan secara tidak langsung terhadap intention to use melalui trust. This study aims to explain a comprehensive model that explains the impact of perceived security and perceived ease of use in influencing intention to use and how they contribute through trust in the context of using digital payment applications in Jakarta. The purpose of this study is to analyze the effect of perceived security on trust, the effect of perceived ease of use on trust, the effect of perceived security on intention to use, the effect of perceived ease of use on intention to use, the effect of trust on intention to use, the effect of perceived security on intention to use through trust, the effect of perceived ease of use on intention to use through trust, as well as the influence of perceived security on intention to use indirect effect through trust and the influence of perceived ease of use on intention to use indirect effect through trust in the use of digital payment applications. Data was collected by using questionnaires online methods to reduce the impact of the covid 19 virus during a pandemic. The object of this research is 150 respondents who are users of digital payment applications. Data analysis to test the validity and reliability using SPSS version 24 and using the Structural Equation Model (SEM) research method with AMOS version 24 to process research data. The results of hypothesis testing show: that perceived security has a significant effect on trust, perceived easeof use has a significant effect on trust, perceived security has a significant effect on the intention to use e payment, perceived ease of use has a significant effect on the intention to use e[1]payment. Trust has a significant effect on the intention to use e payment. Perceived security has a direct significant effect on the intention to use through trust, perceived ease of use does not have a direct significant effect on the intention to use through trust. Perceived security has a significant indirect effect on the intention to use through trust, and perceived ease of use has a significant indirect effect on the intention to use through trust. Abstrak Penelitian ini bertujuan untuk menjelaskan model komprehensif yang menjelaskan pengaruh dampak perceived security dan perceived ease of use dalam mempengaruhi intention to usedan bagaimana kontribusinya melalui trust dalam konteks penggunaan aplikasi pembayaran digital di Jakarta. Tujuan dari penelitian ini dimaksudkan untuk menganalisis pengaruh perceived security terhadap trust, pengaruh perceived ease of use terhadap trust, pengaruh perceived security terhadap intention to use, pengaruh perceived ease of use terhadap intention to use, pengaruh trust terhadap intention to use, pengaruh perceived security terhadap intention to use melalui trust pengaruh perceived ease of use terhadap intention to use melalui trust, serta pengaruh perceived security terhadap intention to use secara tidak langsung melalui trust dan pengaruh perceived ease of use terhadap intention to use secara tidak langsung melalui trustpada penggunaan aplikasi pembayaran digital. Pengumpulan data dilakukan dengan menggunakan metode penyebaran kuesioner secara online untuk mengurangi dampak penyebaran virus covid 19 selama pandemi. Objek penelitian ini berjumlah 150 responden yang merupakan pengguna aplikasi pembayaran digital. Analisis data untuk uji validitas dan reliabilitas menggunakan SPSS versi 24 dan menggunakan metode penelitian Structural Equation Model (SEM) dengan AMOS versi 24 untuk mengolah data penelitian. Hasil pengujian hipotesis menunjukkan: perceived security berpengaruh signifikan terhadap trust, perceived ease of use berpengaruh signifikan terhadap trust, perceived security berpengaruh signifikan terhadap intention to use e payment, perceived ease of use berpengaruh signifikan terhadap intention to use e payment. Trust berpengaruh signifikan terhadap intention to use e[1]payment. Perceived security berpengaruh signifikan secara langsung terhadap intention to usemelalui trust, perceived ease of use tidak berpengaruh signifikan secara langsung terhadap intention to use melalui trust. Perceived security berpengaruh signifikan secara tidak langsungterhadap intention to use melalui trust, perceived ease of use berpengaruh signifikan secara tidak langsung terhadap intention to use melalui trust.